2022
DOI: 10.1038/s41467-022-30336-1
|View full text |Cite
|
Sign up to set email alerts
|

Direct and real-time observation of hole transport dynamics in anatase TiO2 using X-ray free-electron laser

Abstract: Carrier dynamics affects photocatalytic systems, but direct and real-time observations in an element-specific and energy-level-specific manner are challenging. In this study, we demonstrate that the dynamics of photo-generated holes in metal oxides can be directly probed by using femtosecond X-ray absorption spectroscopy at an X-ray free-electron laser. We identify the energy level and life time of holes with a long life time (230 pico-seconds) in nano-crystal materials. We also observe that trapped holes show… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
25
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(26 citation statements)
references
References 47 publications
1
25
0
Order By: Relevance
“…The CBM and VBM are located at Γ (0.0, 0.0, 0.0) and X (0.0, 0.0, 0.5) points. The indirect nature of the band gap is thus indicated which is also consistent with previous theoretical researches [43]. To further reveal the mechanism of the low electrical conductivity of TiO2 in detail, the charge densities around the Fermi level is analyzed as shown in Fig.…”
Section: Electronic Structure Of Tiosupporting
confidence: 85%
“…The CBM and VBM are located at Γ (0.0, 0.0, 0.0) and X (0.0, 0.0, 0.5) points. The indirect nature of the band gap is thus indicated which is also consistent with previous theoretical researches [43]. To further reveal the mechanism of the low electrical conductivity of TiO2 in detail, the charge densities around the Fermi level is analyzed as shown in Fig.…”
Section: Electronic Structure Of Tiosupporting
confidence: 85%
“…Previously, Bruninghoff et al indicated that PL decay is primarily ascribed to the recombination of the immobile holes with free or shallow trapped electrons. 16 of Bruninghoff et al 17 These results also suggest that long-lived photoinduced charge carriers facilitate the photocatalytic process.…”
Section: Introductionmentioning
confidence: 78%
“…To elucidate how the enzyme catalyzed the decolorization of melanin, the interaction between melanin films before and after decolorization was investigated using an SFA. SFA is a device that can measure interaction forces ( F ) and absolute distance ( D ) between two macroscopic surfaces with resolutions of 10 –8 N and 10 –10 m, respectively. , It has been utilized for decades to measure the physical forces of various types of molecules, including proteins, carbohydrates, lipids, polymers, and supramolecules . In this work, the adhesion energy between the melanin or decolorized melanin films was evaluated using an SFA2000 (Surforce LLC, Goleta, USA).…”
Section: Resultsmentioning
confidence: 99%